Semblanza de la Prof. Ana María Fernández Caraballo (1967-2023) - Díaz Genis, Andrea; Behetti , Paola; Capocasale, Alejandra; Medina , Beatriz; Ferreira , Gabriela; de los Santos Montenegro , Adriana; Nuñez , Máximo; Barraco , Natalia; Gauna , Paula (Wimb Lu, 2023)
Sin resumen